“Canales de distribución en comercialización del plátano y fréjol en el mercado mayorista cuatro de mayo de la ciudad de Babahoyo” - Escobar Jaramillo, Brenda Jhomara (2019)
SUMMARY The practical work of complex examination of the titling process to opt for the title of Agricultural Engineer, was developed in the wholesale market Cuatro de Mayo located in the City of Babahoyo University Avenue and By Pass south of the capital of Fluminense. To obtain the results, it was decided to conduct a survey directed to merchants and producers, taking into account that each participant should not have been working in the wholesale market Cuatro de Mayo for less than five years; There were a total of 23 people surveyed, of which 15 banana and bean traders and 8 producers were taken into account. Of the producers to whom the survey was conducted, 80% of them offer the wholesale market merchants Cuatro de Mayo banana mostly the Dominican plantain hartón. 60% of producers mention that the highest production generated by their crops are in the months of: May, September and December, while 40% allude that their crops yield higher production results in the months of: February, April, August, and November. And the remaining months of January, March, July and October banana crops do not generate enough to meet the needs of traders in the market under study. It is worth mentioning that all the banana producers that offer what they obtain from their crops to the wholesale market Cuatro de Mayo belong to the province of Los Ríos. The plantain producers 'crops do not handle it in a technified way, therefore, the investments made are minimal because they do not invest in workers' hands because they own small areas of plantain, the investments are only for the purchase of agroproducts that nourish their crops. plantations and for the control of diseases such as the case of black sigatoka control it with the work of defoliation. Reason why their investments do not exceed USD 100.00 USD per hectare. With yields of 58 bunches that offer them to the merchants: Wholesalers, stores and commercials twice a week at a price of 2.00 Usd US dollars per bunch, of which for self-consumption they take one bunch per harvest. Of the people who sell their premises or stalls in the Cuatro de Mayo market in the city of Babahoyo, 70% of them offer their banana customers. The merchants mention that there is greater supply in the months of May, August, September and November; Times in which clusters can obtain them up to 1.50 Usd US dollars due to the large amount of supply of the product by farmers. Filling your cellars with quantities between 35 to 100 banana bunches. Of the total of the surveyed producers, 20% of them are dedicated to growing beans, offering the wholesalers of the Cuatro de Mayo wholesale market what they obtain in their harvests. It is important to mention that the beans that the farmers offer are in dry grain coming from Ibarra, the producers also mention that the biggest productions occur in the months of May, July and August; reaching up to 10 sacks of beans per hectare, because having land no larger than 2 hectares and agricultural practices developed in their crops are manual without the need to use machinery, therefore, their investments per hectare are not greater than 100.00 Usd american dollars. Offering its products at 80.00 Usd dollars the sack to the wholesale merchants and stores twice a week, taking from its production for self-consumption only 20 pounds of dry bean grain per harvest. Keywords: Distribution channel, marketing, banana, beans, market